Efektivitas Kompres Aloe Vera dan Daun Kubis terhadap Breast Engorgement pada Ibu Nifas - Martini, Martini; Anggraini, Yetti; Septiani, Ranny (Jurnal Kesehatan, 2022)
The problem that often occurs in post-partum mothers after giving birth is the occurrence of breast swelling where there is a narrowing of the lactiferous ducts or the glands are not completely emptied or due to abnormalities in the nipples such as blisters or sinking nipples. Aloe vera gel compresses and cabbage leaves are useful to help reduce pain, swelling, and tenderness in wounds. This study aims to analyze aloe vera compresses and breast care compared to cabbage leaf compresses and breast care on breast swelling in postpartum mothers. This study used a quasi-experimental design with a pre-test post-test non-randomized control group design. The non-probability sampling technique is a consecutive sampling type. The research sample for each group was 15 respondents at one of the Central Lampung Health Centers in June-October 2020. The type of data analysis was the Mann-Whitney test. The results showed that the average swelling of the breasts before being given an aloe vera compress was 4.53 and the average after being given an aloe vera compress was 2.47. The mean breast swelling before compressing cabbage leaves was 5.00 and after compressing cabbage leaves was 3.60. Giving aloe vera compresses is effective in preventing breast swelling in postpartum mothers with a p-value